Critical Breakthrough to Overcome Chaos in Metaphysical, Theological, and Scientific Viewpoints - Seran, Alexander (Journal of Posthumanism, 2025)
This article examines critical breakthroughs to overcome chaos in metaphysical, theological, and scientific viewpoints. This chaos often arises due to differences in paradigms in understanding reality, truth, and the relationship between science, theological beliefs, and metaphysical reflection. Through an analytical and integrative approach, this article examines the potential for harmony between viewpoints by utilizing interdisciplinary theories, such as critical epistemology and the philosophy of reconciliation. The results of the study show that collaboration between disciplines can be an effective solution in bridging the gap in thinking that has been a major challenge. This article offers a new conceptual framework to build a productive and complementary dialogue between the three domains, thus paving the way for a more comprehensive and inclusive understanding. Conclusion implications of the rejection of epistemological and methodological pluralism broaden the anarchic behavior of intellectuals in the Vienna Circle who reject metaphysical-theological arguments in all their manifestations in the fields of literature, philosophy, theology, and anything that is packaged a priori as a meaningless, nonsense, and unvalidated (proven) statement. This is the form of epistemological and methodological anarchism that is opposed by contemporary scientists such as Kuhn, Popper, Feyerabend, Lakatos, Lyotard, Rorty, Barthes, and Habermas.